Patch testing with the European baseline series fragrance markers: a 2016 update. (1st March 2018) - Ung, C.Y.; White, J.M.L.; White, I.R.; Banerjee, P.; McFadden, J.P.
Summary: Fragrance contact allergy is a common cause of allergic skin reactions that can cause eczema. Contact allergy can develop by repeated skin exposure to allergens over time. Fragrance contact allergy is diagnosed by patch testing (applying known allergens to the skin to assess for reactions). In the EU, cosmetic products are regulated to limit the exposure to known allergens. Furthermore, there is a requirement to label cosmetic products that contain any of 26 known individual fragrance allergens to help consumers avoid those allergens to which they are allergic. In most dermatology departments in the UK, instead of patch testing to all 26 individual fragrance allergens, fragrance contact allergy is diagnosed by patch testing to 4 screening markers: Fragrance Mix I, Fragrance Mix II, Myroxylon pereirae and hydroxyisohexyl 3‐cyclohexane carboxaldehyde. In this study, the authors reviewed 2084 records of patients with eczema who underwent patch testing to all the individual fragrance allergens, as well as the screening markers of fragrance allergy, to find out the proportion of actual fragrance contact allergy detected by testing only to the screening markers. They found that patch testing only to the screening markers detected 40.8% of patients with actual fragrance contact allergy (patients who were diagnosed with fragrance allergy when additionally tested with individual fragrance allergens). They also found that the majority of patients with fragrance contact allergy were not aware that they developed skin reactions upon exposure to fragrances. The authors concluded that the current screening markers used are not sufficient for the diagnosis of fragrance contact allergy.